Intense Bodily Presence Practices of Polish Butō Dancers - Zamorska, Magdalena Anna (Interdisciplinary Studies in Performance, 2018)
The author explores the practices of Polish butō dancers. Underlining the transcultural potential of the genre, she discusses in particular their individual body-mind practices and so-called butō techniques in order to produce a generalised account of butō training. Her argument is underpinned by complex field research which she carried out as an expert observer and a workshop participant. Drawing on a transdisciplinary approach, which combines insights and findings from the fields of cultural and performance studies, cultural anthropology and cognitive sciences, the book depicts the sequence of three phases which make up the processual structure of butō training: intro, following and embodiment.